Baking the Nation: Women as Nation-Builders in 19th Century Colombia - Blanco Estupiñán, Angélica María (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article explores how women contributed to theconstruction of the nation through the transformation ofculinary culture. Women from both elite and popular sectors undertook to change daily habits with the aim of creating a modern society that could foster the republican project. The article analyses the changes in eating habits, the position of women in society, and how they adapted the consumption of European goods and recipes. Consequently, the article delves into the roles women played in shaping a new national identity during the 19th century.